The Coming Liberal Arts Wave in India - Pushkar (International Higher Education, 2022)
India’s higher education sector is likely to witness a liberal arts wave in the 2020s. The National Education Policy 2020 emphasizes multidisciplinary education as the path forward. This is also expected to boost the employability of college graduates. However, it will not happen without a broader set of reforms across the higher education sector—in areas such as governance, regulatory structures, institutional autonomy, and others—to improve the overall quality of college education.